Susceptibilidad antibiótica de bacterias aisladas de urocultivos de pacientes atendidos en el Hospital Regional Docente de Trujillo – La Libertad, 2019 - Revilla Melendez, Cris Jenifer (2019)
This study determined the frequency and antibiotic susceptibility of uropathogens isolated from patients with urinary tract infections at the Hospital Regional Docente de Trujillo. From January to March 2019, 105 cultures were obtained and sown in Nutrient Agar plates at the hospital’s microbiology laboratory to be further transported to the Microbial Physiology and Genetics Laboratory of the Universidad Nacional de Trujillo, where they were incubated at 37ºC for 18 hours. Samples were taken from reactivated strains to proceed with bacterial suspension at 0.5 MacFarland turbidity scale for 15 minutes, then sown on a Mueller Hinton Agar plate ensuring uniform inoculum distribution. Eight different antibiotic discs were added and plates were incubated at 35 ° C in an aerobic atmosphere for 18 hours. The most frequently isolated uropathogen was E. coli in 68.57%, followed by K. pneumoniae, P. mirabilis, P. aeruginosa and A. baumannii. Regarding the frequency of antibiotic susceptibility of E. coli cultures, 100% were sensitive to imipenem and 68.05% to amikacin, whileas 73.61% and 70.83% of the crops were resistant to ceftriaxone and ciprofloxacin, respectively. The totality of K. pneumoniae and Proteus mirabilis cultures were sensitive to imipenem and ampicillin/sulbactam, amikacin, gentamicin and tobramycin respectively. On the contrary, 100% P. aeruginosa cultures were resistant to ampicillin / sulbactam, ceftriaxone and trimethoprim / sulfamethoxazole. Finally, 100% of A. baumannii isolates were resistant to ampicillin / sulbactam, gentamicin, ciprofloxacin and trimethoprim / sulfamethoxazole.